Paying Taxes 2014 : The Global Picture - PricewaterhouseCoopers; World Bank Group (World Bank Group, Washington, DC, 2014)
Paying Taxes 2014 looks at tax regimes in 189 economies as part of the Doing Business series. The period covered by the study, 2004 to 2012, has seen the end of a sustained period of economic growth, a severe recession and a slow recovery. Governments continue to be under the pressure balance the need to attract investment and foster growth while generating tax revenues. This report finds that governments continue to reform their tax systems despite global economic uncertainty, with 32 economies having taken steps from June last year through May 2013 to make it easier and cost less for small and medium businesses to pay taxes. The report finds that the most common tax reform undertaken by 11 economies is the introduction or improvement of electronic filing, eliminating the need for 74 separate tax payments and reducing compliance time by almost 200 hours in total. On average around the world it now takes our case study company 268 hours to comply with its taxes, it makes 26.7 payments and has an average total tax rate of 43.1 percent. The range for each sub-indicator is very wide. The number of payments ranges from 3 in Hong Kong SAR, China and Saudi Arabia to 71 in República Bolivariana de Venezuela. The time to comply is lowest in the United Arab Emirates where it takes 12 hours to deal with the taxes that apply, all of which are labor taxes. The highest number of hours is still taken by our company in Brazil. It takes 2,600 hours with more than half of this time being spent on consumption taxes. Until 2008, 7 of the 8 geographical regions covered in the report had consistently recorded a fall in their average total tax rate. This changed in 2009 when only 5 regions recorded a fall. This fell to 3 in 2011 and in the latest study only Africa and South America show a fall in the total tax rate while all other regions show an increase apart from Asia Pacific and EU and EFTA where rates of 36.6 percent and 42.5 percent respectively have been maintained. Over the nine years of the study the total tax rate attributable to profit taxes have fallen faster than that for labor taxes so that labor taxes are now the largest element of the total tax rate. While the average time to comply has fallen by 55 hours over the 9 years of the study, the rate of decline has slowed dramatically in the most recent period, falling by only 1 hour between 2011 and 2012. Over the nine years of study, the greatest improvement on time has been seen for labor taxes (23 hours). The number of hours has fallen by 19 hours for consumption taxes and by 13 hours for corporate income tax.